EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA SD NEGERI TRI MULYA AGUNG - Tiara Kusnaedi; Nila Kesumawati; Adrianus Dedy (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Understanding a mathematical concept is the ability of a person to understand and understand and can construct concepts with rules so that it is easy to understand can also re-express abstract ideas. The study is aimed at seeing the effectiveness of the cooperative learning model make a match type to enhance understanding of the mathematical concept of students in the Tri Mulya Agung class of students. The study is carried out in the Tri Mulya Agung state elementary class V. The study themed quantitative research and experimentation using two classes of control classes and experiment classes. Independent Sampel T-Test collection techniques used by tests. The results of the latest research show a cooperative learning model make a match effective in ami increase the understanding of the mathematics concepts of students in the nation's Tri Mulya Agung school in 60.50 experiments and 43.80 control classes. This proves the cooperative learning model make a match effectively enhances student mathematical concepts. Keywords: Make A Match Model, Mathematics